Managing Leave of Absence from the Healthcare Facility for Voluntarily Hospitalized Persons with Mental Illness: Ethical and Legal Perspectives (TEST BioLaw Journal - Rivista di BioDiritto, 2026)
In this article, we examine the ethical and legal implications of leave of absence for people with mental illness who are voluntarily admitted to psychiatric healthcare facilities. Rather than framing the issue as a conflict between personal freedom and safety, we draw on the concept of relational autonomy and the practice of positive risk-taking to develop an approach that balances protection and self-determination as part of the therapeutic process. We describe practical strategies for implementing this model, including individualized planning, risk assessment, and the active engagement of those involved in the patient’s care. Finally, we discuss how clinical ethics consultation can support shared decision-making in this context.
Keywords: psychiatry; self-determination; relational autonomy; positive risk-taking; clinical ethics consultation